Monte Carlo simulations of microchannel plate detectors. I. Steady-state voltage bias results - Wu, Ming; Kruschwitz, Craig A.; Morgan, Dane V.; Morgan, Jiaming (Review of scientific instruments, 2008)
X-ray detectors based on straight-channel microchannel plates (MCPs) are a powerful diagnostic tool for two-dimensional, time-resolved imaging and time-resolved x-ray spectroscopy in the fields of laser-driven inertial confinement fusion and fast Z-pinch experiments. Understanding the behavior of microchannel plates as used in such detectors is critical to understanding the data obtained. The subject of this paper is a Monte Carlo computer code we have developed to simulate the electron cascade in a MCP under a static applied voltage. Also included in the simulation is elastic reflection of low-energy electrons from the channel wall, which is important at lower voltages. When model results were compared to measured MCP sensitivities, good agreement was found. Spatial resolution simulations of MCP-based detectors were also presented and found to agree with experimental measurements.